Multi-Sine EIS for Early Detection of PEMFC Failure Modes - Fortin, Patrick; Gerhardt, Michael R.; Ulleberg, Øystein; Zenith, Federico; Holm, Thomas (Frontiers in Energy Research, 2022)
Electrochemical impedance spectroscopy (EIS) is a powerful technique that can be used to detect small changes in electrochemical systems and subsequently identify the source of the change. While promising, analysis is often non-intuitive and time-consuming, where collection times of a single EIS spectrum can reach several minutes. To circumvent the long collection times associated with traditional EIS measurements, a multi-sine EIS technique was proposed in which the simultaneous application of many frequencies can reduce the acquisition time to less than a minute. This shortened acquisition time opens the possibility to use multi-sine EIS as a real-time diagnostic tool for monitoring the state-of-health of commercial fuel cell systems. In this work, a single-cell proton exchange membrane fuel cell (PEMFC) was characterised using multi-sine EIS, by establishing steady-state impedance response under baseline conditions before systematically changing operating conditions and monitoring the dynamic changes of the impedance response. Our initial results demonstrate that full multi-sine EIS spectra, encompassing a frequency range from 50 kHz to 0.5 Hz, can be collected and analysed using simple equivalent circuit models in 50 seconds. It is shown that this timeframe is sufficiently short to capture the dynamic response of the fuel cell in response to changing operating conditions, thereby validating the use of multi-sine EIS as a diagnostic technique for in-situ monitoring and fault detection during fuel cell operation.